Partial Heart Transplantation for Congenital Heart Disease. A Narrative Review of Current Knowledge and Future Directions - Widomska, Katarzyna; Bernad, Mateusz; Bender, Aleksandra; Walczak, Paulina; Niewęgłowska, Małgorzata; Szymulewicz, Bartłomiej; Dąbrowski, Kacper; Łukaszewicz, Jakub; Krazińska, Oliwia; Gałach, Magdalena; Figiel, Aniela; Zaborek, Paweł; et al. (Quality in Sport, 2026)
Background. Partial heart transplantation (PHT), also referred to as living valve replacement, is an emerging surgical strategy for irreparable valvular defects. By implanting viable donor valve tissue, PHT provides grafts capable of somatic growth, addressing a key limitation of conventional prosthetic valves in pediatric patients, in whom the lack of growth potential necessitates repeated reoperations. Aim. This review aims to introduce the concept of partial heart transplantation to a broader clinical audience and to summarize current clinical experience. We discuss indications, technical considerations, and organizational challenges associated with PHT in infants, and outline potential applications in older children and adults. Methods. A structured literature search was conducted in databases using selected keywords related to partial heart transplantation and congenital heart disease. Because the available evidence remains early and heterogeneous, a narrative review approach was adopted with SANRA quality criteria. The included literature consisted mainly of case reports, case series, and review articles. Results. The largest reported case series included 19 patients who underwent PHT between April 2022 and December 2024. Replacement of semilunar valves was associated with significant annular growth and preserved valvular function during follow-up. At the time of publication, none of the transplanted valves required explantation due to graft failure. Early observations suggest that, owing to the relatively low immunogenicity of cardiac valves, immunosuppressive requirements after PHT may be lower than those required after orthotopic heart transplantation. Conclusion. Evidence for PHT is currently limited to small cohorts with short follow-up. Multicenter collaboration and standardized registry-based data collection will be essential to define indications, evaluate long-term outcomes, and establish the role of PHT within contemporary valve replacement strategies.